Selo Soemardjan Sang Penerjemah: Subjektivitas dalam Asal-Usul Cara Berpikir Sosiologis di Indonesia - Geger Riyanto (Antropologi Indonesia, 2011)
This paper was written against a background of interest to trace the formation of sociological ways of thinking that tend to legitimize power in Indonesia. During the preparation, I found problems in the perspective commonly used in researching the formation process of knowledge; knowledge is considered a form of power. Such approach is problematic because it denies subjectivity – which includes cognitive activity and experiences that are owned only by the existence of the related – absolute in the process of both producing and reproducing knowledge. Yet this criticism isn’t easy to elaborate because the question is, how do we insert subjectivity when the origins of sociological thinking that we’re talking about is an effort to continue in a non-reflective way of sociology in the U.S. in the Cold War era, who’s way of thinking MENATURALISASI the existing social order and its ideology. Finally, I placed Selo Soemardjan – a figure that became the center of this analysis because of his irreplaceable role in institutionalizing sociological ways of thinking (U.S.) in Indonesia – as a translator. Quoting Bruno Latour’s view (1987), only with exploring the process of dissemination of knowledge as an activity of translation can we find energy that has been invisible all this time in a variety of knowledge analysises. For me, this concept helps reveal subjectivity that has been buried by views that place actors as passive mediums in the forming or spreading of knowledge that is more true or beneficial in preserving structure. Keywords: Selo Soemardjan, knowledge, power, translation, subjectivity, sociological ways of thinking